Effects of 12 Months Continuous Positive Airway Pressure on Sympathetic Activity Related Brainstem Function and Structure in Obstructive Sleep Apnea - Henderson, Luke A.; Fatouleh, Rania H.; Lundblad, Linda C.; McKenzie, David K.; Macefield, Vaughan G. (Frontiers in Neuroscience, 2016)
Muscle sympathetic nerve activity (MSNA) is greatly elevated in patients with obstructive sleep apnoea (OSA) during normoxic daytime wakefulness. Increased MSNA is a precursor to hypertension and elevated cardiovascular morbidity and mortality. However, the mechanisms underlying the high MSNA in OSA are not well understood. In this study we used concurrent microneurography and magnetic resonance imaging to explore MSNA-related brainstem activity changes and anatomical changes in 15 control and 15 subjects with OSA prior to and following 6 and 12 months of continuous positive airway pressure (CPAP) treatment. We found that 6 and 12 months of CPAP treatment significantly reduced the elevated resting MSNA in individuals with OSA. Furthermore, this MSNA reduction was associated with restoration of MSNA-related activity and structural changes in the medullary raphe, rostral ventrolateral medulla, dorsolateral pons and ventral midbrain. This restoration occurred after 6 months of CPAP treatment and was maintained following 12 months CPAP. These findings show that continual CPAP treatment is an effective long-term treatment for elevated MNSA likely due to its effects on restoring brainstem structure and function.